Mechanics of biological systems and materials & micro-and nanomechanics. proceedings of the 2019 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2019 Annual Conference on Experimental and Applied Mechanics. Volume 4 : (2020) - Unknown
No abstract available